Exploring nursing students' experiences of blindness simulation: A phenomenological study - Alireza Nikbakht Nasrabadi; Masoumeh Malek; Mahboubeh Shali; Haleh Jafari (Wiley, 2022)
Abstract Aim The aim of this study was to explore the experiences of blindness simulation among a group of nursing students. Design This qualitative study was conducted using an interpretive phenomenological method. Methods Using purposeful sampling method, students were informed and invited to participate in the research through the Website of Tehran School of Nursing and Midwifery. We listed the candidates and until data saturation and compilation of the study, 8 students entered the study. They shared their experiences about blindness simulation through individual in‐depth and semi‐structured interviews. We continued the interviews until the data were saturated. The transcribed interviews were analysed by Colaizzi's approach. Results The results of data analysis resulted in three major themes and nine sub‐themes, which were conceptually named based on their nature. The major themes included abandoned in the labyrinth puzzle, vision of heart and self‐alienation.